Predicting Long-Term Outcome after Endovascular Stroke Treatment: The Totaled Health Risks in Vascular Events Score - Flint, A.C.; Cullen, S.P.; Faigeles, B.S.; Rao, V.A. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Endovascular treatments are being increasingly used in acute ischemic stroke, and better tools are needed to determine which patients may benefit most from these techniques. We hypothesized that specific chronic diseases can be used, along with age and stroke severity, to predict endovascular stroke treatment outcomes. MATERIALS AND METHODS: Data from 2 single-arm trials of a thrombectomy device, MERCI and Multi MERCI, were pooled for analysis. A predictive score was developed by using the independent contribution of variables in multivariable analysis. RESULTS: HTN, DM, and AFib were found to predict outcomes. These 3 conditions contribute equally to a CDS that predicts outcomes independent of other predictor variables, including age, stroke severity, and vessel recanalization. A 10-level predictive score, the THRIVE score, which incorporates age, stroke severity, and the CDS, was developed. The THRIVE score strongly predicts outcome and mortality at 90 days. CONCLUSIONS: Specific chronic diseases influence poststroke outcomes among patients undergoing endovascular stroke treatment, independent of other predictors of outcome. The THRIVE score reflects the contributions of chronic disease, age, and stroke severity and strongly predicts endovascular stroke treatment outcomes. AFibhistory of atrial fibrillationASPECTSAlberta Stroke Program Early CT ScoreCADhistory of coronary artery diseaseCDSchronic disease scaleCHFhistory of congestive heart failureCholhistory of hypercholesterolemiaCIconfidence intervalDMhistory of diabetes mellitusGLMgeneralized linear modelHTNhistory of hypertensionMERCIMechanical Embolus Removal in Cerebral IschemiamRSmodified Rankin ScaleMulti MERCIMulti Mechanical Embolus Removal in Cerebral IschemiaNIHSNational Institutes of Health Stroke ScaleORodds ratioPROACTProlyse in Acute Cerebral ThromboembolismPseudo-R2pseudo R-squaredROC AUCreceiver-operating characteristic area under the curveRRrisk ratioTHRIVETotaled Health Risks in Vascular Events scoreTobhistory of active tobacco smokingtPAtissue plasminogen activator